Life-Expectancy Disparities Among Adults With HIV in the United States and Canada: The Impact of a Reduction in Drug- and Alcohol-Related Deaths Using the Lives Saved Simulation Model. Issue 12 (11th October 2019) - Althoff, Keri N; Chandran, Aruna; Zhang, Jinbing; Arevalo, Wendy Miranda; Gange, Stephen J; Sterling, Timothy R; Gill, M John; Justice, Amy C; Palella, Frank J; Rebeiro, Peter F; Silverberg, Michael J; Mayor, Angel M; et al.
Abstract: Improvements in life expectancy among people living with human immunodeficiency virus (PLWH) receiving antiretroviral treatment in the United States and Canada might differ among key populations. Given the difference in substance use among key populations and the current opioid epidemic, drug- and alcohol-related deaths might be contributing to the disparities in life expectancy. We sought to estimate life expectancy at age 20 years in key populations (and their comparison groups) in 3 time periods (2004–2007, 2008–2011, and 2012–2015) and the potential increase in expected life expectancy with a simulated 20% reduction in drug- and alcohol-related deaths using the novel Lives Saved Simulation model. Among 92, 289 PLWH, life expectancy increased in all key populations and comparison groups from 2004–2007 to 2012–2015. Disparities in survival of approximately a decade persisted among black versus white men who have sex with men and people with (vs. without) a history of injection drug use. A 20% reduction in drug- and alcohol-related mortality would have the greatest life-expectancy benefit for black men who have sex with men, white women, and people with a history of injection drug use. Our findings suggest that preventing drug- and alcohol-related deaths among PLWH could narrow disparities in life expectancy among some key populations, but other causes of death must be addressed to further narrow the disparities.